Effects of cigarette smoke and tobacco heating aerosol on color stability of dental enamel, dentin, and composite resin restorations - Zanetti, Filippo; Zhao, Xiaoyi; Pan, Jie; Peitsch, Manuel C.; Hoeng, Julia; Ren, Yanfang (Actual Dentistry, 2020)
Objectives: to test if cigarette smoke (CS) causes discoloration of enamel, dentin, and composite resin restorations and induces color mismatch between dental hard tissues and the restorations, and to compare the findings with the effects of aerosol generated by the tobacco heating system (THS) 2.2. Method and materials. Twenty-two human premolars were prepared with Class V cavities restored with Filtek Supreme Ultra (3M Espe) composite resin. Teeth were divided into two groups and exposed to either CS from 20 reference cigarettes (3R4F) or aerosol from 20 THS 2.2 tobacco heat sticks 4 days a week for 3 weeks. CIE L*a*b* color was assessed before and after exposure and brushing at 1, 2, and 3 weeks. Color match, marginal discoloration, marginal integrity, and surface texture of the Class V restoration were assessed according to a modified US Public Health Service (USPHS) criterion. Results. Marked discoloration of enamel and dentin was observed following 3 weeks of CS exposure (ΔE = 8.8 ± 2.6 and 21.3 ± 4.4, respectively), and color mismatch occurred between the composite resin restorations (ΔE = 25.6 ± 3.8) and dental hard tissues. Discoloration was minimal in the enamel, dentin, and composite resin restorations in the THS 2.2 group, and no color mismatch was observed after 3 weeks of THS 2.2 aerosol exposure. Conclusion. CS causes significant tooth discoloration and induces color mismatch between dental hard tissues and composite resin restorations. Reducing or eliminating the deposits derived from tobacco combustion could minimize the impact of tobacco products on tooth discoloration. Key words: dental restoration failure, dentin, enamel, filling materials, smoking, tooth discoloration